Environmental & architectural phenomenology. Vol. 34, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2023)
This issue is a memoriam for humanistic geographer Yi-Fu Tuan, who died in August 2022. The issue includes tributes by philosopher Ingrid Leman Stefanovic and geographers Edward Relph, Stanley Brunn, and Xu Huang. We include excerpts from four of Tuan’s many articles, chapters, and books. This winter/spring issue also includes one book review and three essays:
Cognitive scientist Andrea Hiott reviews psychiatrist Iain McGilchrist’s 2009 The Master and His Emissary.
Zoologist Stephen Wood considers the phenomenon of noticing the natural world and the question of how this directed awareness unfolds.
Anthropologist Jenny Quillien provides a first-person ethnography of her recent residence in Alaska.
Religious-studies scholar Harry Oldmeadow discusses the sacredness of deserts, a theme that complements his earlier EAP essay on the holiness of mountains.
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals